The Relationship between Natural Gas Consumption and Economic Growth in Egypt - Mohamed, Manar; Helmy, Omneia; Ibrahiem, Dalia M. (New Energy Exploitation and Application, 2025)
Given the increasing reliance on natural gas as a primary energy source in Egypt and its pivotal role in supporting industrial production and electricity generation, understanding the relationship between natural gas consumption and economic growth is of great importance. This is particularly crucial in the context of energy policy formulation, sustainable development, and efficient resource allocation. This study investigates the causal nexus between natural gas consumption and economic growth in Egypt during the period from 1988 to 2018. The primary aim is to determine whether economic growth drives gas consumption or vice versa, which carries significant implications for energy policy and sustainable development planning. The research adopts the Auto Regressive Distributed Lag (ARDL) approach to analyze long-term relationships, while the Vector Error Correction Model (VECM) Granger causality test is employed to explore short-run and long-run causal dynamics between the variables. The empirical findings reveal a unidirectional causality running from economic growth to natural gas consumption in the short run, supporting the conservation hypothesis. This suggests that economic expansion leads to increased gas consumption, but not the other way around. In contrast, no causality is detected in the long run, aligning with the neutrality hypothesis, which implies that natural gas consumption does not significantly influence long-term economic growth.